A contrastive phonology of Tamil, Telugu, Kannada and Malayalam based on distinctive features - N, Somusundaran (Journal of All India Institute of Speech and Hearing, 1972)
Speech pathology deals with the understanding, assessment, and treatment of speech and language disorders. This necessitates a good understanding of the case who is to be treated, the problem the case has and in addition, the language to be taught. The situation in India, with its multiplicity of linguistic groups, presents itself additional problems in that the speech clinician may have to work with languages non-native to him. Even if the therapist is a native speaker of the language with which he has to work, it is important for the speech clinician to have a clear understanding of his own speech Recently there has been great emphasis on distinctive feature analysis of speech. Attempts are now being made to programme articulation therapy based on distinctive features